Will Climate Change the Future of Homeland Security - Wasp,Valli A (2016)
Drought, melting Arctic ice, ocean acidification, and sea-level rise are all subsectors of climate change. I have identified these as slow-onset disasters. The purpose of this thesis is to determine whether slow-onset disasters are adequately addressed in the homeland security discipline. Risk assessments were performed to determine the level of risk these types of disasters pose to homeland security. The critical infrastructure lifeline sectorsEnergy, Communications, Transportation Systems, and Water and Wastewater Systemswere chosen for these assessments because of their identified criticality to national security. The assessments reveal slow-onset disasters pose varying degrees of risk to these sectors. Policy analyses were conducted on the components of the nations coordinated approach to homeland security. These reveal the homeland security discipline does not adequately address slow-onset disasters because of internal contradictions. The contradictions are the result of two of the frameworks used in the development of homeland security policiescontinuity heuristic and probabilistic thinking. These frameworks lead disaster-consequence planners to consider the probability and magnitude of a disaster based on a retro-focused approach. Based upon my findings, I recommend that possibilistic reasoning (anticipating the worst that could happen), coupled with a future-focused approach, be used to develop homeland security policies that will fully address the emerging threats posed by slow-onset disasters.